تحليل جغرافي للخصائص الجغرافية (الطبيعية والبشرية) في محافظات الفرات الأوسط وعلاقاتها المكانية في التخصص الإقليمي - الموسوي، علي صاحب طالب Almousawi, Ali Saheb Taleb; مكي، منيرة محمد (جامعة الكوفة - كلية التربية للبنات, 2007)
The present thesis was performed to detailed and accurate study of geographical, especially natural and humanity, characteristics and their spatial relationship with regional specialization of Middle Euphrates governorate. The thesis composed of five chapters. First chapter was detected the theoretical framework and it was explain The concepts and terms related to region meanings. kinds of regions, and manner of determination each of them, in addition to regional and agricultural specialization. - The second chapter deals with natural characteristics of the study region, through out focusing on the geographical and astronomical location, geological structure, topographic and climatic state, features of soil, water resources and natural plants of middle Euphrates region, These characteristics tend to consistency at their nature. The third chapter was concerning with humanity characteristics (demographic characteristics) which included population distribution, age and sex structure and with the most important Economic characteristics which comprised agricultural activity and agricultural manner of Middle Euphrates governorate. the most crops were planted and potential specialization of this region in planting this crops. On the other hand. extend on industrial activity. transportation, tourism, and religious tourism. which were marked by their temporal fluctuation. The fourth chapter was focused on applicable part which included the statistical analysis (quantitative) of correlation relationships between studied governorates, to rising a territorial and temporal unity of region. It was included statistical analysis of natural characteristics, in the front of them, are the climatic features, which compromise the cornerstone of natural unity of region, in addition to. the economic features were represented by population, and agricultural activity which includes planted area, production and yield per denim. From which the region was obtained its justification for economic completeness as organic and constructive unit included alternate influences and interactions . The study was ended by detailed analysis of natural and humanity characteristics and represented the homogeneity and specialization of Middle Euphrates legion including those characteristics in two important points: first. The territorial relationship between natural characteristics and regional specialization. The second point was centered on humanity (population, urbanite, and economic) characteristics of region and their relationships with population unity, homogeneity, economic specialization and their role in regional specialization.
Keywords: النشاط الاقتصادي -- الموارد الطبيعية -- الموارد البشرية -- العراق -- الأحوال الاقتصادية -- السكان -- الأحوال الاجتماعية -- الزراعة -- المناخ -- التربة -- الموارد المائية -- التضاريس -- الأمطار -- الرياح -- الرطوبة -- مصادر المياه -- نهر الفرات -- النمو السكاني -- المحاصيل الزراعية